Green entrepreneurial intentions in Saudi youth: cultural insights and implications - Hashed Mabkhot; Yahdih Semlali; Hamid Mahmood Gelaidan; Nadia A. Abdelmegeed Abdelwahed; Hasnizam Shaari (Discover Sustainability)
Abstract This study investigates green entrepreneurial intentions (GEI) and behaviors among Saudi Arabian youth, examining the influence of contextual factors such as entrepreneurial education, university environmental support, and entrepreneurial motivation. Using the Theory of Planned Behavior (TPB) as a foundational framework, this research contributes novel insights by contextualizing GEI within Saudi Arabia’s unique socio-cultural landscape and Vision 2030, a national initiative focused on economic diversification and sustainability. Data were collected from a sample of 441 university students and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Key theoretical contributions of this study include expanding TPB by integrating environmental and motivational factors specific to Saudi youth, thereby offering a nuanced understanding of how cultural and institutional contexts shape green entrepreneurial intentions. Practically, the findings underscore the importance of embedding sustainability-focused entrepreneurship into educational curricula and suggest policy strategies to foster green entrepreneurship. This study offers critical insights for educators, policymakers, and entrepreneurs aiming to align Saudi Arabia’s youth entrepreneurship initiatives with sustainable development goals, reinforcing the role of young entrepreneurs as drivers of a sustainable future.